(3TQM HOjYI GdHjGf Yf ehJ GdCYjGfs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG TQM ef GdUOhQ s
(3BNQgG (B:s
(3BNQ HOjYI GdHjGf Yf ehJ GdCYjGf s
(3CQLhRI ai hajGJ GdCYjGf TQMgG hJQLe ddePchQjf ajgG hGdTQM hGdeJf cdGgeG dgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B76 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B159 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJGQjNs